Linking neighbors' fertility: Third births in Norwegian neighborhoods - Janna Bergsvik (Comparative Population Studies (CPoS), 2020)
Geographical variations in fertility and the diffusion of fertility across space and social networks are central topics in demographic research. Less is known, however, about the role of neighborhoods and neighbors with regard to geographical variations in fertility. This paper investigates spatial variations in family size by analyzing third births in a neighborhood context. Using unique geo-data on neighbors and neighborhoods, this paper introduces a new geographical dimension of fertility variation and contributes to our understanding of geographical variations in fertility. Flexible, ego-centered neighborhoods are constructed using longitudinal geo-data taken from administrative registers (2000-2014). Data on inhabitants' residential address, their housing, family situation and fixed effects for statistical tracts are used to account for sorting into housing and urban versus rural districts. The analysis shows that the likelihood of two-child couples having another child increases with the share of families in the neighborhood that have three or more children. This relationship remains unchanged, even after controlling for the sociodemographic characteristics of couples, the educational level attained by neighboring women as well as time-constant characteristics of neighborhoods. Results are consistent across various neighborhood definitions ranging from the 12 to the 500 nearest neighbors. However, the association between neighbors' fertility becomes stronger as the number of neighbors increases, suggesting that selective residential sorting is an important driver. Consequently, this study indicates that transitions to third birth may be linked to social interaction effects among neighbors, in addition to well-known processes of selective residential sorting.
urn:nbn:de:bib-cpos-2020-21en4
Keywords: 300; Spatial fertility; k-nearest neighbors; Fertility diffusion; Family size; Third births